Representações da ditadura civil militar em livros didáticos de história: uma análise crítica do discurso - Mendonça, Ateniense Alves de (2014)
The present research was proposed to this: analyze critically the speeches and its power relations. For that, had as object of study LDHs fit for the ninth grade of elementary school. Thus, we intend to investigate, specifically, as the historical fact of the Civil-Military Dictatorship of Brazil is represented in two didactic works. The first production is edited, in 2009, the Brazilian Army's own library, the collection of Aldo and authorship Trompowsky Marshal Demerval Rio Branco, Maurício de Siqueira, Mallet Soares, Neide Annarumma, entitled History of Brazil: Empire and Republic. The second work, by contrast, does not have any link with the Brazilian Army, being produced in 2011, a large national circulation Publisher, Editora Moderna, written by a single author, Patricia Ramos Braick, and its title: Study History of the origins of man in the digital age. From this, it will be discussed the thought of Norman Fairclough (2001), British linguist, founder of icon critical analysis. The work of the author contributes significantly to the establishment and development of Critical Discourse Studies, in that it introduces a different analytical method, the so-called "three-dimensional model of discourse analysis", which places text instances, discursive practice and social practice as a fully dialectical dimensions and bases for the look of investigative analyst of speeches. According to the British theorist, the text form and is formed in the social practices, being those domains are interconnected and mutually constituted.